2020
DOI: 10.3390/microorganisms8020169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Profound Feedstock Change on the Structure and Performance of Biogas Microbiomes

Abstract: In this study the response of biogas-producing microbiomes to a profound feedstock change was investigated. The microbiomes were adapted to the digestion of either 100% sugar beet, maize silage, or of the silages with elevated amounts of total ammonium nitrogen (TAN) by adding ammonium carbonate or animal manure. The feedstock exchange resulted in a short-range decrease or increase in the biogas yields according to the level of chemical feedstock complexity. Fifteen taxa were found in all reactors and can be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Members within this phylum are proposed to have the capacity to use both amino acids and carbohydrates and to perform propionate oxidation (Johnson & Hug, 2022 ; Westerholm et al, 2022 ). In previous studies on biogas processes, this phylum has been suggested as a biomarker for process disturbance (Klang et al, 2019 , 2020 ; Singh, 2021 ; Singh, Moestedt, et al, 2021 ; Singh, Müller, & Schnürer, 2021 ). In the present study, the reduced abundance of families belonging to phylum Ca .…”
Section: Discussionmentioning
confidence: 99%
“…Members within this phylum are proposed to have the capacity to use both amino acids and carbohydrates and to perform propionate oxidation (Johnson & Hug, 2022 ; Westerholm et al, 2022 ). In previous studies on biogas processes, this phylum has been suggested as a biomarker for process disturbance (Klang et al, 2019 , 2020 ; Singh, 2021 ; Singh, Moestedt, et al, 2021 ; Singh, Müller, & Schnürer, 2021 ). In the present study, the reduced abundance of families belonging to phylum Ca .…”
Section: Discussionmentioning
confidence: 99%
“…3b). Klang et al [31] tested the effects of changing environments (e.g., exchanging sugar beet silage for maize silage and vice versa) on the biogas microbiomes. While the archaeal communities did not change during their 8-week test phase after the feedstock change, the bacterial communities adapted.…”
Section: High-resolution Volatile Fatty Acid Patternmentioning
confidence: 99%
“…The degradation of propionic acid into educts for methane formation (acetate, formate, or hydrogen) is characterized by an unfavorable thermodynamic balance. Thus, this reaction is only possible when the cleavage products are directly used further by acid-degrading methanogens and require a close syntrophic relationship between both groups of microorganisms [31,[34][35][36]. The presence of acetateproducing bacteria (using H 2 and CO 2 ) also leads to favorable thermodynamics as H 2 partial pressure is kept low [37].…”
Section: High-resolution Volatile Fatty Acid Patternmentioning
confidence: 99%
“…The feedstock addition could be well controlled to be the same and periodical across the AD process. Due to these advantages, AD has been used as a model system to understand microbial community assembly under changes in feedstock or sludge properties [9,10], reveal microbial community assemblage differences among replicated reactors [11], and predict digestor performance based on operational parameters [12]. These advantages of the AD system provide a unique opportunity to address the above questions and hypotheses (Fig.…”
Section: Introductionmentioning
confidence: 99%